THE ASSESSMENT OF BANDUNG TRIGA REACTOR TANK RADIOACTIVITY IN THE PERIOD 2000-2014 USING ORIGEN-2 - Sudjatmi Kustituantini Alfa; Reinaldy Nazar; Ketut Kamajaya; Putranto Ilham Y (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2017)
THE ASSESSMENT OF BANDUNG TRIGA REACTOR TANK RADIOACTIVITY IN THE PERIOD 2000-2014 USING ORIGEN-2            In accordance with the regulation of the regulatory body of Indonesia related to the decommissioning of nuclear reactors, the management of the Bandung TRIGA reactor have to prepare a decommissioning plan document of the Bandung TRIGA research reactor. Decommissioning program documents shall be regularly updated every five years of the operation of nuclear reactor. In year 2000, Bandung TRIGA reactor tank have been lined using aluminum alloy 6061-T6 and has activated during reactor operation. Aluminum alloy 6061-T6 contains impurities that can produce high radioactivity and has a long half-life. This paper describes the radioactivity of the reactor tank after activation during the period from 2000 to 2014 using the software ORIGEN-2. Total radioactivity of the reactor tank bottom after decay for 5 years was 1.83 10-7 Curie, while the total radioactivity of reactor tank wall was 3.2 10-3 Curie.